Spacecraft formation control using aerodynamic and Lorentz force. Issue 4 (16th March 2020) - Sun, Ran; Shan, Aidang; Zhang, Chengxi; Jia, Qingxian
Abstract : Purpose: This paper aims to investigate the feasibility of using the combination of Lorentz force and aerodynamic force as a propellantless control method for spacecraft formation. Design/methodology/approach: It is assumed that each spacecraft is equipped with several large flat plates, which can rotate to produce aerodynamic force. Lorentz force can be achieved by modulating spacecraft's electrostatic charge. An adaptive output feedback controller is designed based on a sliding mode observer to account for unknown uncertainties and the absence of relative velocity measurements. Aiming at distributing the control input, an optimal control allocation method is proposed to calculate the electrostatic charge of the Lorentz spacecraft and control commands for the atmospheric-based actuators. Findings: Numerical examples are provided to demonstrate the effectiveness of the proposed control strategy in the presence of J2 perturbations. Simulation results show that relative motion in a formation can be precisely controlled by the proposed propellantless control method under uncertainties and unavailability of velocity measurements. Research limitations/implications: The controllability of the system is not theoretically investigated in the current work. Practical implications: The proposed control method introduced in this paper can be applied for small satellites formation in low Earth orbit. Originality/value: The main contribution of the paper is the proposal of the propellantless control approach for satellite formation using the combination of Lorentz force and aerodynamic force, which can eliminate the requirement of the propulsion system.